Raízes e rumos: reflexões sobre identidades de guianenses em Boa Vista - Roraima - Brito, Maria Lúcia da Silva (2012)
This work aims to reflect about the relationship between language and identity in Guyanese immigrants who live in the urban area of Boa Vista - the capital of Roraima. It is a search under the bias of Applied Linguistics because it is a transdisciplinar field that allowed the dialogue with other areas of knowledge such as History, Geography, Social Sciences, Literature, Music, Cultural Studies, Social Psychology, Law and Discourse Analysis. The records were collected through the development of field diary and semi-structured interviews of nine audio-recorded and duly authorized by the subjects. Then, I wrote the scripting of interviews to find the data. From the reflection raised by the research question "How does language influence the identity formation of immigrant Guyanese living in Boa Vista - RR?", I wrote the text presenting both theories that base this work and subjects involved. Then, I elaborated a reflexive analysis about the language in use by immigrants,about being Guyanese according to Law and on the perceptions of themselves and others in the game's language "here" and "there".